Economic Determinants of Government Subsidies - Clements, Benedict (IMF Working Papers; Working Paper ;, 1998)
The paper studies the economic determinants of government subsidies using panel data for 40 countries over 18 years (from 1975 to 1992) and finds that individual country-specific factors play a sizeable role in determining government subsidies. But it also suggests several characteristics-a small government, a small external current account deficit, and a productive structure geared more toward services and agriculture than manufacturing-may make it easier to keep subsidy expenditures down. The paper also suggests that globalization and the associated increase in openness are not impediments to reducing subsidies. In itself, an IMF-supported adjustment program is found not to be a significant determinant of government subsidy expenditures.